PENGARUH KARAKTERISTIK KOMITE AUDIT TERHADAP FINANCIAL RESTATEMENTS (Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia (BEI) pada Tahun 2016) - Intan, Chyntia Margareth; Azwir, Nasir; Desmiyawati, Desmiyawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This study aims to examine the effect of audit committee characteristics onfinancial restatements. Audit committee characteristics used in this study areaudit committee independence, audit committee meeting, audit committee size,and audit committee expertise. The population in this study is all companies listedon Indonesia Stock Exchange (IDX) in 2016. Research sample is determined usinga purposive sampling method. The data in this research is obtained by annualreports of 27 companies that have restated their financial restatements and 27companies that did not restate their financial restatements, resulting in a total of54 samples. This study uses the Logistic Regression as a method of analysis. Theresults prove that audit committee expertise influence financial restatements.Meanwhile, audit committee independence, audit committee meeting, and auditcommittee size have no significant effect on financial restatements.Keywords: audit committee, corporate governance, financial restatements